Analysis of Biomass Content of Bottom Plants and Biomass Litter on Agroforestry Land with Slash and Buring System - Syarif Ohorella; Mira Herawati Soekamto (Tropical Small Island Agriculture Management, 2021)
In this land use, humans act as ecosystem regulators, namely by getting rid of components that he considers useless or by developing features that are expected to support their land use (Mather, 1986; Gandasasmita, 2018), which is a residue and others that can increase soil fertility levels such as soil organic matter, biomass, and necromass. This study aims to measure the biomass content of lower plants and litter biomass on agroforestry land with a slash and burn system. Before and after the combustion process, the ten soil samples showed more C-organic content before the combustion treatment, with a total C-organic of 8.16% - 7.8% = 0.36% C-organic released. The organic matter available before burning is more when compared to after burning, which is 14.05% - 13.43% = 0.62% of the organic matter released. Biomass litter contained wet weight 2500g – 3910g dry weight = -1410 grams of carbon emitted.